2021
DOI: 10.32890/mjli2021.18.2.9
|View full text |Cite
|
Sign up to set email alerts
|

An Exploratory Sequential Sentiment Analysis of Online Learning During the Movement Control Order in Malaysia

Abstract: Purpose – Online learning is an essential platform to support varying learning conditions, anytime and anywhere. It helps connect online communities regardless of one’s geographical location and time zone. During the COVID-19 outbreak in Malaysia, the use of online learning platforms has become a crucial option for accomplishing learning objectives. During this challenging time, universities have been looking for suitable solutions to address issues regarding the online learning process. This paper discusses t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…), student-respondents conceded that they seek assistance from friends, family, and even teachers, as well as from reading informative books or using printed materials, searching for dictionaries and going to libraries or otherwise by requesting more from the top management and notifying the school principal about this matter. Abdul Rahman et al (2021) revealed that learners from rural areas needed help joining their online classes and sometimes could not join due to a lack of access to the internet. Sahu (2020) supported that learners who do not have access to the Internet may have difficulties with tests and evaluations.…”
Section: Challenges and Coping Strategies Of Students On Lack Of Acce...mentioning
confidence: 99%
“…), student-respondents conceded that they seek assistance from friends, family, and even teachers, as well as from reading informative books or using printed materials, searching for dictionaries and going to libraries or otherwise by requesting more from the top management and notifying the school principal about this matter. Abdul Rahman et al (2021) revealed that learners from rural areas needed help joining their online classes and sometimes could not join due to a lack of access to the internet. Sahu (2020) supported that learners who do not have access to the Internet may have difficulties with tests and evaluations.…”
Section: Challenges and Coping Strategies Of Students On Lack Of Acce...mentioning
confidence: 99%